Design of a 20,000 Pound Variable Stiffness Actuator for Structural Vibration Attenuation - John Leavitt; James E. Bobrow; Faryar Jabbari (Shock and Vibration)
This paper describes the design of a novel actuator capable of protecting a full scale structure from severe load conditions. The design includes a cylinder filled with pressurized nitrogen and uses commercially available components. We demonstrate that the actuator behaves like a spring with an adjustable unstretched length, and that the effective spring stiffness can be changed easily by changing the initial cylinder pressure. In order to test the actuator on a full scale structure, an effective spring constant of approximately 10,000 pounds/inch was required over a two inch stroke. Because of the spring-like behavior, rather than damper-like behavior, the actuator does not transmit high forces to a vibrating structure like linear viscous dampers do when velocities are high. We analyze features of critical importance to the design of the actuator such as the cylinder dimensions, operating pressure, and valve selection. We then investigate the performance using a novel experimental apparatus that mimics the dynamics of a single story building, but has 1/400 the weight.